Synthesis, crystal structure and photochromic property of a phenethyl viologen bismuth(III) chloride. Issue 4 (16th February 2019) - Wang, Yu-Lin; Chen, Xiao-He; Shu, Wen; Qin, Hao-Ge; Lin, Jian-Di; Lin, Rong-Guang; Wen, Na
Abstract: Viologen bismuthate halides generally show photochromic properties. In the present work, phenylethyl alcohol was introduced into chloro bismuthates in the hope to prepare photochromic crystalline materials and finally a photochromic inorganic-organic hybrid, (PeV)3 (Bi2 Cl9 )2 (1 ), based on an in situ generated PeV 2+ cation (PeV 2+ = phenethylviologen = N, N ′-diphenethyl-4, 4′-bipyridinium), has been obtained, whose microstructure contains a discrete dimer [Bi2 Cl9 ] 3– counterion identified by single crystal X-ray diffraction. More importantly, 1 exhibits a typical photochromic behavior, which can be mainly attributed to the reversible inter-conversion between the monocation viologen radical [PeV] + and the viologen dication [PeV] 2+ .